2015
DOI: 10.1186/s12889-015-2621-5
|View full text |Cite
|
Sign up to set email alerts
|

Skewed risk perceptions in pregnant women: the case of influenza vaccination

Abstract: Background: Pregnant women and their newborns have an increased risk of developing severe influenza and influenza-related complications. In Germany, seasonal influenza vaccination is recommended for pregnant women since 2010. However, little is known about pregnant women's vaccination-related knowledge and attitudes, as well as their risk perceptions. This study therefore assessed pregnant women's vaccination-related knowledge, risk perceptions related to influenza disease and influenza vaccination during preg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
1
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 40 publications
4
26
1
2
Order By: Relevance
“…Specifically, of the 40% that received a recommendation and an offer of influenza vaccination, 95% were vaccinated; however, among those who received neither a vaccination recommendation nor an offer, only 5% were vaccinated. This finding supports the literature that healthcare provider recommendation and offer of influenza vaccination are leading predictors of vaccination among pregnant women [612] and substantiates that healthcare providers with up-to-date knowledge, good practices and attitudes towards influenza vaccination foster acceptance of the vaccine among pregnant women [13,14]. …”
Section: Discussionsupporting
confidence: 85%
“…Specifically, of the 40% that received a recommendation and an offer of influenza vaccination, 95% were vaccinated; however, among those who received neither a vaccination recommendation nor an offer, only 5% were vaccinated. This finding supports the literature that healthcare provider recommendation and offer of influenza vaccination are leading predictors of vaccination among pregnant women [612] and substantiates that healthcare providers with up-to-date knowledge, good practices and attitudes towards influenza vaccination foster acceptance of the vaccine among pregnant women [13,14]. …”
Section: Discussionsupporting
confidence: 85%
“…Therefore, it is important to design and to implement interventions in order to increase the vaccination rate. The value observed in the present study is higher than those reported in other countries, since no women had received influenza vaccination in the already mentioned study in India [34], 3% in Turkey [36], 4% in Thailand [26], and it is almost identical to the 6% in Iran [37], 10.9% in Germany [38], and 16% in Canada [39]. Whereas, it is substantially below the levels observed in Australia with an uptake of 27% [20], in France of 39% [40], in Belgium of 42.8% [41], and in the United States with levels ranging from 35% [14] to 66.4% [42].…”
Section: Discussioncontrasting
confidence: 68%
“…Women of older age had higher level of knowledge and, not surprisingly, those with higher education level were more likely to know that the influenza is dangerous for pregnant women and to report a positive attitude towards the utility of the vaccination during pregnancy. Prior study has shown similar findings [38]. The fact that women with a high-risk pregnancy were more likely to know that the influenza is dangerous for pregnant can serve as a focus when promoting health education interventions.…”
Section: Discussionsupporting
confidence: 66%
“…Trotzdem sind die Impfraten in dieser Hochrisikogruppe der Schwangeren in Deutschland gering, für das Jahr 2014 wurde nur eine Impfrate von 10,6 % ermittelt [6]. Weiterhin weisen Studien darauf hin, dass das Wissen unter Schwangeren und werdende Eltern über Impfungen unzureichend und von Fehlvorstellungen geprägt ist [7]. Weiterführende Untersuchungen belegen zudem, dass Impfentscheidungen neben subjektiver Wahrnehmung auch durch Internetrecherche beeinflusst werden.…”
Section: Introductionunclassified